2009
DOI: 10.1080/08897070903250084
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Relapse Prevention for Substance Use Disorders: A Pilot Efficacy Trial

Abstract: The current study is the first randomized-controlled trial evaluating the feasibility and initial efficacy of an 8-week outpatient Mindfulness-Based Relapse Prevention (MBRP) program as compared to treatment as usual (TAU). Participants were 168 adults with substance use disorders who had recently completed intensive inpatient or outpatient treatment. Assessments were administered pre-intervention, post-intervention, and 2 and 4 months post-intervention. Feasibility of MBRP was demonstrated by consistent homew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
541
1
16

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 615 publications
(584 citation statements)
references
References 71 publications
15
541
1
16
Order By: Relevance
“…MindfulnessBased Stress Reduction (MBSR; Kabat-Zinn, 1990), which might be seen as a precursor and US counterpart 3 to MBCT, is practiced at over 240 hospitals and clinics worldwide (Baer, 2003) with over 19,000 participants having completed the program since 1979 (Center for Mindfulness, 2009). More recently, Mindfulness-Based Relapse Prevention (Bowen et al, 2009) has been developed as a group program for preventing relapse following rehabilitation for substance use disorders. Mindfulness techniques are also widely utilized in numerous one-to-one therapeutic modes such as Dialectic Behaviour Therapy (Linehan, 1993) and Acceptance and Commitment Therapy (Hayes, Strosahl & Wilson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…MindfulnessBased Stress Reduction (MBSR; Kabat-Zinn, 1990), which might be seen as a precursor and US counterpart 3 to MBCT, is practiced at over 240 hospitals and clinics worldwide (Baer, 2003) with over 19,000 participants having completed the program since 1979 (Center for Mindfulness, 2009). More recently, Mindfulness-Based Relapse Prevention (Bowen et al, 2009) has been developed as a group program for preventing relapse following rehabilitation for substance use disorders. Mindfulness techniques are also widely utilized in numerous one-to-one therapeutic modes such as Dialectic Behaviour Therapy (Linehan, 1993) and Acceptance and Commitment Therapy (Hayes, Strosahl & Wilson, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent pilot efficacy trial of MBRP used as an aftercare following intensive substance misuse treatment showed increased acceptance and reduced substance use and craving, especially in response to depression [29,30]. A randomized trial comparing standard relapse prevention to MBRP in part of a residential addiction treatment programme for women offenders found that MBRP resulted in fewer drug using days and fewer medical and legal problems [31].…”
Section: Mindfulness-based Relapse Prevention For Addictionmentioning
confidence: 99%
“…In the first subpopulation with sensitivity to self-discrepancy, therapists could identify patients' personal values and help to establish action in line with these values. Moreover, increasing self-acceptance (e.g., mindfulness [29,30]) is important to reduce distress caused by selfdiscrepancy. In the second subpopulation, it could be interesting to increase AD patients' awareness of self-related elements to (re)connect to their Self during therapeutic process (e.g., psychoeducation, etc.…”
Section: Conclusion and Clinical Perspectivesmentioning
confidence: 99%